Pedagogos e a construção do conhecimento sobre alfabetização cartográfica nos anos iniciais do ensino fundamental - Budel, Marli Rosa (2009)
The present work makes a theoretical approach relating different areas of the knowledge as the Geography, Cartography and Psychology. The students' indifference about Geography discipline is noticed in the last years of the Fundamental Teaching, where the same has wide dimension out of the classroom and it is present in the students' day by day. With that intention the student’s teacher has a fundamental paper in the process of construction of the knowledge. He is the mediator between the student and the contents, promoting the interaction of the same ones. The best form of diagnosing the root of the problem took us to the contact with students educators of Santa Maria's Federal University that study the 8th semester and they were accomplishing their apprenticeships close to the students of the years begin of the Fundamental Teaching. The several works of professionals' researches that study subjects related to the cartographic literacy importance, considered as basic notions for the geographical learning. The research data were obtained through the application of questionnaires. With that, we obtain a lot of information that allowed a quantitative analysis of the results through tables. Those data were systematized with the concern of the students’ educators' reality knowing in formation. The necessary basic prerequisites development for the map understanding elements were noticed with certain deficiency by part of the futures professional starting from the analysis. Through the activities evaluation was noticed that in spite of the educators to have a small notion ABOUT THE cartographic literacy observed in the program of one of the disciplines of the course, they still have a lot of difficulties in relating with the practice the one that are submitted. It was noticed that the presented gaps happen during the formation process and it feels in function maybe for the lack of a discipline that develops the practice relating the theory. Therefore, the indifference verified among the students of the final years happens due the notions about cartographic literacy was not overcome in the initial years. The work is divided in four way that in the first is the introduction, the second treat of the respectively in the theoretical fundamentation (The Geographical space and the Cartography; Map Elements; the child’s built space motion and his development); the methodology ( the research type and the Pedagogy course; material and method); the analysis of result and the final considerations.